Functional resource of irony in modern media discourse (based on correspondence on the social networking site Facebook) - Kurjanovich А.В. (Bulletin of L.N. Gumilyov Eurasian National University. JOURNALISM Series, 2019)
The objectives of the study include the study of the functional properties of irony as a means of creating a comic effect in epistolary media-network texts - polylogic correspondence of users of the social network Facebook. The multifunctional essence of irony, functioning in the space of modern media communication, is revealed. As a research method, elements of discursive analysis, lexico-semantic, communicative-pragmatic and stylistic analysis are used. The study, based on achievements in the field of modern theory of media communication, cognitive-discursive linguistics, theory of epistolary, found that irony is one of the most popular means of representing the communicative strategy of epistolary addressees, aimed at creating a comic effect. An analysis of the empirical material showed that irony in online correspondence contributes to the expression of the author’s reflection on the acute social problems that exist in society. Irony implements the estimated, affecting, characterizing, phatic, coordinating, cognitive functions. A thesis is put forward on the prevalence in the list of functional properties of irony of the function of conceptualizing the speaker of knowledge about the world and of expressing one’s own attitude to this knowledge.